Solubility measurement and modelling of 1, 8-dinitronaphthalene in nine organic solvents from T = (273.15 to 308.15) K and mixing properties of solutions. (November 2015) - Zhou, Guoquan; Du, Cunbin; Han, Shuo; Meng, Long; Wang, Jian; Li, Rongrong; Zhao, Hongkun
Graphical abstract: Highlights: Solubility of 1, 8-dinitronaphthalene in nine organic solvents were determined. The solubility were correlated with Apelblat equation, Wilson and NRTL model. The mixing properties of solution were calculated based on the Wilson model. Abstract: The solubility of 1, 8-dinitronaphthalene in acetonitrile, methanol, ethanol, trichloromethane, isopropanol, acetone, toluene, ethyl acetate and butyl alcohol were obtained experimentally at temperatures ranging from (273.15 to 308.15) K under 0.1 MPa by using a gravimetric method. The solubility of 1, 8-dinitronaphthalene in those solvents increases with an increase in temperature. The solubility values decrease according to the following order: acetone > (acetonitrile, ethyl acetate) > trichloromethane > toluene > methanol > ethanol > isopropanol > butyl alcohol. Three models, the modified Apelblat equation, Wilson and NRTL were used to correlate the solubility of 1, 8-dinitronaphthalene in the solvents studied. The calculated solubility by the modified Apelblat equation provides better agreement than those evaluated by the other two models. The regressed results via the three models are all acceptable for the solubility of 1, 8-dinitronaphthalene in the selected solvents. Furthermore, the mixing Gibbs energy, mixing enthalpy, and mixing entropy for per 1 mol of mixture of 1, 8-dinitronaphthalene and solvents were calculated based on the Wilson model. The dissolution process of 1, 8-dinitronaphthalene in the selected solvents is spontaneous and exothermic.